Emergency Caesarean Section: Influences on the Decision-to-Delivery Interval. (12th June 2011) - Cerbinskaite, Aiste; Malone, Sarah; McDermott, Jennifer; Loughney, Andrew D.
Abstract : RCOG/NICE guidelines recommend that, for fetal compromise in labour, delivery should be accomplished ideally within 30 minutes. In this study, we investigated the factors which affect the decision-to-delivery (DD) intervals for emergency caesareans. To achieve this, prospective data were collected for all grade 1 and 2 caesareans performed on a busy labour ward over 12 months. We found that the ratio of labouring women to midwives had a significant effect on the DD intervals, which were significantly prolonged when 1 : 1 care was not provided (P < 0.001 ). The observed effect resulted exclusively from a prolonged transfer time to theatre. General anesthesia use shortened the DD interval for grade 1 caesareans (P < 0.001 ) and was more likely to be used during the day shift (P < 0.009 ). We conclude that midwifery staffing levels and the form of anaesthesia employed influence on DD intervals for the most urgent caesarean sections.